Catalytic transfer hydrogenation and characterization of flash hydrolyzed microalgae into hydrocarbon fuels production (jet fuel). (1st February 2020) - Asiedu, Alexander; Davis, Ryan; Kumar, Sandeep
Graphical abstract: Highlights: Oil-laden biofuel intermediate from flash hydrolysis was characterized. Optimization of the oil extraction was executed using 2-propanol. Trimetallic catalyst was prepared and characterized. Extracted oil was subjected to CTH reaction using 2-propanol as in-situ H-donor. Kinetics of CTH was performed to estimate kinetic parameters. Abstract: Oil-laden biofuel intermediate (BI) from flash-hydrolyzed microalgae was characterized, pyrolyzed, and subjected to catalytic transfer hydrogenation (CTH) to produce both gaseous and liquid hydrocarbon fuels. The BI was characterized by TGA and FTIR that revealed significant triglyceride, evidenced by CO bond with insignificant level of carbohydrates and proteins. Thermogravimetric analysis (TGA) indicated that the BI could be thermally decomposed at 400 °C. Pyrolysis of the BI engendered mainly gaseous hydrocarbon (alkenes) with high heating value (HHV) of 48.5 kJ/mol at 850 °C. Energy of activation for the pyrolytic process was estimated to be 115–300 kJ/mol. Optimization of oil extraction from the BI was performed via design of experiment. The oil was subjected to CTH over NiOx -CoOx -MoOx -zeolite using 2-propanol as hydrogen donor in a 30-ml batch reactor at a temperature range of 390–420 °C and autogenic pressure of 24–27 bar, leading to fatty acid conversion of 99–100%. The main liquid products obtained from the CTH were iso -alkanes (41%), cyclo -alkanes (35%), aromatics (5%), n-alkanes (14%), and alkenes (5%). Kinetics of the CTH showed first order with activation energy of 176 kJ/mol. The catalyst was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Brunaeur-Emmett-Teller (BET) adsorption and desorption, scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), and TGA. The catalyst revealed cubic structure, which was maintained after 5 h of CTH reaction. Present in both the fresh and the used catalysts were oxides of alkali and transition metals. The active sites of the catalyst were dominated by Co 3+, Ni 2+, and Mo 6+ .